Numerical prediction of interference factor in motions and added resistance for Delft catamaran 372 - Dogrul, Ali; Kahramanoglu, Emre; Cakici, Ferdi (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Multi-hull forms are widely used in maritime applications such as passenger transport and military operations. These vessels' hydrodynamic characteristics may differ from the displacement type ships. This matter makes multi-hull hydrodynamics an important research field to study. Regarding this, the authors focused on the numerical investigation of Delft catamaran 372 that is widely used for benchmarking. Unsteady RANS analyses were conducted at Fr = 0.3 in regular head wave conditions. The numerical approach was first verified and then validated with the available experimental data in terms of calm water resistance and vertical motions. The main highlights of this study are the comprehensive validation study with the literature and the calculation of the interference factor (IF) through total and added resistance in waves. Motion and added resistance transfer functions were obtained for catamaran and demihull geometries. It is concluded that the effects of interference factor in waves are highly important in catamaran forms.
Keywords: Added resistance; RANS; Delft catamaran; Interference factor; Vertical motions; Engineering; Oceanography